Engineered Living Materials: Prospects and Challenges for Using Biological Systems to Direct the Assembly of Smart Materials - Nguyen, Peter Q. (Adv Mater, 2018)
Vast potential exists for the development of novel, engineered platforms that manipulate biology for the production of programmed advanced materials. Such systems would possess the autonomous, adaptive, and self-healing characteristics of living organisms but would be engineered with the goal of assembling bulk materials with designer physicochemical or mechanical properties, across multiple length scales. Early efforts towards such Engineered Living Materials (ELMs) are reviewed here, with an emphasis on the engineered bacterial systems, living composite materials which integrate inorganic components, successful examples of large-scale implementation, and production methods. In addition, a conceptual exploration of the fundamental criteria of ELM technology and its future challenges is presented. Cradled within the rich intersection of synthetic biology and self-assembling materials, the development of ELM technologies will allow us to leverage the power of biology to grow complex structures and objects using a palette of bionanomaterials.